Optimization of Student Grade Data Management Using RESTful API and Microservices Architecture : Case Study at Universitas Mitra Indonesia - hartanto, M. Budi; Fawaati, Teuku Muhammad; Fahurian, Fatimah; Yunita, Hilda Dwi; Zuhri, Khozainuz (CCIT (Creative Communication and Innovative Technology) Journal, 2025)
The management of student grade data is a critical component of academic information systems that require high efficiency and reliability. At Universitas Mitra Indonesia, the old monolithic system faced challenges in scalability, security, and accessibility. This study proposes the implementation of RESTful API and microservices architecture to optimize the management of student grade data. RESTful API serves as the primary interface for inter-service communication, while microservices allow for independent management of modules such as user authentication, grade data processing, and academic service provision. Implementation results demonstrate a 35% increase in data access speed, a 25% reduction in server load, and enhanced security through token-based authentication. This study significantly contributes to modernizing academic information systems, especially in improving the performance and scalability of digital academic services.